Management of the National Health Insurance Scheme by HMOs: Determining the Workability of the Mechanisms Involved - Katuka, Yaki; Emmanuel, Emelda Ifeanyi; Sampson, Joseph Maren (NIU Journal of Social Sciences, 2020)
The health maintenance organizations - national health insurance scheme design in health care is an arrangement or mechanism employed to ensure a successful implementation of the NHIS itself. However, the processes involved in managing the enrollees through this arrangement may be complex and tasking. But because both organizations share similar goals, partnering may be possible. The study therefore focused on the role of HMOs and how they can facilitate the National Health Insurance Scheme. The essence was to find out if they can work together. The study utilized the quantitative and qualitative methods to gather information from respondents. The survey method was used to obtain responses from 384 respondents in the study and nine in-depth interviews were conducted with key officials of important organizations in the scheme. From the analysis and discussion of the research findings, it was discovered that HMOs played very important roles in the scheme and had significant impact on the scheme. It also discovered that HMOs do not only manage funds meant for the treatment of NHIS enrollees, but reduce the administrative burden of intermediaries for NHIS, HCPs and uses of the scheme. They enable the smooth functioning of the scheme as they effectively discharge their duties. The implication of these findings of the study is that HMOs on a long run, if properly supervised by the NHIS would facilitate the achievement of the goal of universal coverage far beyond stipulated time. Keywords: Health Maintenance Organization, Managed care, Health care, National health insurance scheme.